2021
DOI: 10.1210/endocr/bqab037
|View full text |Cite
|
Sign up to set email alerts
|

Mendelian Randomization Highlights the Causal Role of Normal Thyroid Function on Blood Lipid Profiles

Abstract: The association between thyroid function and dyslipidemia has been well documented in observational studies. However, observational studies are prone to confounding, making it difficult to conduct causal inference. We performed a two-sample bi-directional Mendelian randomization (MR) using summary statistics from large-scale genome-wide association studies (GWASs) of thyroid stimulating hormone (TSH), free thyroxine (FT4) and blood lipids. We chose inverse variance weighted (IVW) method as main analysis, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 69 publications
1
8
0
5
Order By: Relevance
“…In the colocalization analysis, there was little evidence that 2 traits showing evidence of a causal association in the MR analysis were colocalized, which suggested that the SNPs in the gene locus might be LD with proxied variants and might not be suitable for perturbing drug targets, or that multiple causal variants might exist within the given region, which was not suitable for colocalization analysis ( 22 ). Meanwhile, the value of PP.H1 was relatively high, indicating variants in the region were significantly associated with resistin and were unlikely to affect the outcome, thus obeying the MR main assumption and further supporting our MR estimates ( 45 ). Because of the limited summary-level statistics for chemerin and RBP4, colocalization analysis was not performed on the causal associations between chemerin and CAD, RBP4 and HF.…”
Section: Discussionsupporting
confidence: 82%
“…In the colocalization analysis, there was little evidence that 2 traits showing evidence of a causal association in the MR analysis were colocalized, which suggested that the SNPs in the gene locus might be LD with proxied variants and might not be suitable for perturbing drug targets, or that multiple causal variants might exist within the given region, which was not suitable for colocalization analysis ( 22 ). Meanwhile, the value of PP.H1 was relatively high, indicating variants in the region were significantly associated with resistin and were unlikely to affect the outcome, thus obeying the MR main assumption and further supporting our MR estimates ( 45 ). Because of the limited summary-level statistics for chemerin and RBP4, colocalization analysis was not performed on the causal associations between chemerin and CAD, RBP4 and HF.…”
Section: Discussionsupporting
confidence: 82%
“…They explored the genetic association between TSH and serum lipid profiles via Mendelian randomization (MR). According to Wang et al 17 , per 1 standard deviation (SD) increase in normal TSH was significantly associated with a 0.048 SD increase in TC and a 0.032 SD increase in LDL-C, whereas TSH did not show a causal association with HDL-C and TGs. The study by van Vliet et al 18 unveiled a positive association between high TSH within normal range with the levels of very low-density lipoprotein subclasses and components, TGs, and the TG contents in lipoproteins.…”
Section: Discussionmentioning
confidence: 99%
“…MR is established on the basis that if a causal relationship exists between PBC and thyroid dysfunction, the SNP related to PBC will also be related to thyroid dysfunction through the occurrence of PBC, in which case the IVs only associate with PBC, and MR can help establish a causal relationship between PBC and thyroid function (Davey Smith and Hemani, 2014). Also, two-sample MR has been used to explore the causal relationship between thyroid function and breast cancer (Yuan et al, 2020), atrial fibrillation (Ellervik et al, 2019), and blood lipid profile (Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%